Isotopic and hydrochemical insights into the groundwater characteristics along an arid to semi‐humid climate gradient in China - Chen, Peiyuan; Ma, Jinzhu; Ma, Xiaoyi; Zhou, Ying; Duan, Zhihua; Wang, Yueyue; Li, Jisheng (Hydrological processes, 2024)
In arid to semi‐arid regions, groundwater is a critical water resource heavily relied upon, with the recharge sources and patterns being predominantly shaped by climate change and regional disparities. To compare the characteristics of groundwater in the endorheic and exorheic river basins with the climate transition zone of Gansu Province, this study uses isotopic hydrochemical analyses. This study summarizes the differences in regional groundwater recharge and evolutionary patterns. The results shows that the distribution patterns of precipitation isotopes in endorheic and exorheic river basins are opposite to those of groundwater isotopes. Specifically, the precipitation in the endorheic areas is more depleted in heavy isotopes, whereas the groundwater is more enriched. Both endorheic areas and exorheic areas exhibit similar characteristics of groundwater hydrochemical evolution, evolving from low‐mineralization Mg2+HCO3− recharge water to Na+Cl− type water with saline characteristics. The former is primarily replenished by surface water, whereas the latter is primarily replenished by precipitation. Variations in recharge patterns along with the differences in climatic conditions lead to distinct groundwater conditions in the two regions. The spatial distribution patterns of precipitation and groundwater isotopes in the study area are opposite. The primary evolution pathways of groundwater are the transformation of Mg·HCO3 to Na·Cl type. Mainly Groundwater recharge mode:(a) Endorheic basins: surface water; (b) Exorheic basins: precipitation.